Exploring the impact of a story-based teacher training programme on language and early literacy in 4- and 5-year-olds. - O'Carroll, Shelley; Oakhill, Jane; Cain, Kate; Klop, Daleen; Visser, Monique (Wordworks, 2023)
This is the first in a series of five research briefs that explore the impact of Little Stars, a story-based teacher training programme on language and early literacy in 4- and 5-year-olds. This brief focuses on key elements of the programme, and on the design of a study to explore how effective it is. Early Childhood Development (ECD) teachers have a critical role to play in providing language- and print-rich learning experiences for young children. There is a need for evidence-based, contextually relevant teacher development programmes and resources that support quality language teaching. The Little Stars programme was carefully designed to meet the specific needs, characteristics and circumstances of early childhood education in low-resource contexts in South Africa.
Little Stars: A low-cost, open-source language and literacy professional development programme for pre-Grade R teachers.
More information about the Little Stars training programme and materials can be found at: www.wordworks.org.za
Keywords: ECD; storytelling; early language; early literacy; South Africa; teacher development